BSE Sensex Closing Index Data Analysis and Forecasting using the ARIMA Model - Raychaudhuri, Debaditya (International Journal of Computer Sciences and Engineering, 2019)
The Bombay Stock Exchange (BSE) is India’s premier and most prestigious stock market. A stock market is a facilitation centre for trading (buying and selling) of stocks of various companies. Its index is calculated as a combination of stock prices of several companies enlisted in the exchange. The stock market is characterized by its endless and unpredictable troughs and crests. This paper attempts to analyse the BSE Sensex Closing Index data over a span of the last decade collected on the last day of the month (from May, 2009 to April, 2019). It also attempts to predict the BSE Sensex closing data for a future span of 10 years at a monthly frequency. The paper also does a accuracy testing of the predictive model generated. This work would be beneficial for both the nation and a trading individual. The Stock market indices reflect the health of a nation’s economy and its direction and growth. A trading individual would benefit in his pursuit of profit making by taking correct investment decisions based on accurate predictions made. The paper uses the ARIMA model for timeseries analysis and for generating a predictive model for making future forecasts.